The release profiles of Baccaurea angulata extract from various gelling agents - Sukmasari, Susi; Abdul Qader, Omar Abdul Jabbar; Abdul Rahman, Mohammad Nasrin; Ibrahim, Muhammad; Doolaanea, Abd Almonem (PharmaInfo Publications, 2018)
This study investigates the release profiles of Baccaurea angulata extracts incorporated in carbopol, guar gum, and konjac gum. Franz cell diffusion was run for 24h for finite dosing, and 6h for infinite dosing. From finite dosing, carbopol had the highest cumulative amount permeated, (75.75±1.18% content release) compared to guar gum and konjac gum (p<0.05). Carbopol exhibited the fastest release profile with the highest mean flux (29.04±0.74μg/cm2/h) (p<0.05) permeated within the first 0.75h. Konjac gum had faster release behavior compared to guar gum. However, the amount of content release by guar gum was higher compared to konjac gum for the total of 24h (p<0.05). For infinite dosing, the cumulative amount of content released by carbopol was the highest (4095.97±38.70μg) compared to guar gum and konjac gum (p < 0.05). Steady state flux of carbopol was the highest (379.26±3.58 μg/cm2/h) compared to guar gum and konjac gum (p<0.05). Carbopol showed the highest permeability coefficient: 6.20×10-2cm/h compared to guar gum and konjac gum (p<0.05). Guar gum had higher values in all calculated elements compared to konjac gum, except that its content release was slower. Therefore, it is concluded that carbopol has the best release profile to be developed as Baccaurea angulata dental gel.